SISTEM PENDUKUNG KEPUTUSAN PENERIMA BANTUAN PKH (PROGRAM KELUARGA HARAPAN) DENGAN METODE PERBANDINGAN EKSPONENSIAL - Frandy Putra Gusti A.P; Elistya Rimawati; Sri Tomo (Jurnal Ilmiah SINUS, 2023)
The Pelem Village Head Office has several government aids that will be distributed to its citizens. One of the acceptances of “Program Keluarga Harapan” (PKH) in 2019 has several criteria such as the elderly, people with disabilities, pregnant women and dependent children. However, officers have difficulty in processing the data. The purpose of this thesis is to create a decision support system for the selection of beneficiaries of “Program Keluarga Harapan” (PKH) assistance in Pelem Village using the Exponential Comparison Method (MPE). The results of this study are in the form of a decision support system program that has been tested through functional testing of the system using the blackbox testing method. The results of the testing process with the User Acceptance Test (UAT) of the respondents agreed (70%) that the overall decision support system for the recipients of RTLH assistance could assist officers as needed.